Localization of the Lateral Retinacular Nerve for Diagnostic and Therapeutic Nerve Block for Lateral Knee Pain: A Cadaveric Study. Issue 2 (23rd June 2016) - Sutaria, Rakhi G.; Lee, Se Won; Kim, Soo Yeon; Howe, Ruth; Downie, Sherry A.
Abstract: Background: The lateral retinacular nerve (LRN) is a branch of the superior lateral genicular nerve (SLGN) and is believed to contribute to anterolateral knee pain. The precise anatomical pathway of the LRN, however, has not been demonstrated as it relates to the performance of targeted nerve block procedures. Objective: To describe the anatomical landmarks for localization of the LRN to facilitate diagnostic and therapeutic nerve blocks in the treatment of chronic anterolateral knee pain. Design: Descriptive study. Setting: Anatomy dissection laboratory in an academic institution. Methods: Twenty lower extremities were dissected in 12 cadavers. The sciatic nerve was identified, and its branch to the posterior aspect of the knee, the SLGN, was dissected. The SLGN dissection was continued distally to identify its first branch, the LRN. Two measurements were taken from the branch point on the lateral knee deep to the distal biceps tendon in alignment with the fibular head. A validation study completed in 4 knees was performed as follows: 1 mL of colored dye was injected at the first and second measurements. The cadaveric knee was then dissected to assess the accuracy. Main Outcome Measurements: Localization of the branch point of the LRN from the SLGN via dissection and then direct assessment of injected dye at the measurement points via dissection. Results: The branch point of the LRN from the SLGN was, on average, 5.5 ± 0.66 cm (with a range of 4.5‐7.0 cm) proximal to the lateral tibiofemoral joint line in line with the head of the fibula and 2.6 ± 0.62 cm (2.0‐4.5 cm) proximal to the tip of the lateral femoral epicondyle. On assessment of the 2 measurements, the measurement 5.5 cm proximal to the lateral joint line accurately targeted the branch point in 100% (4/4) of the knees, whereas the measurement 2.6 cm proximal the tip of the lateral femoral epicondyle accurately targeted the branch point in 75% (3/4) of the knees. Conclusion: The results of this study provide 2 dependable landmarks and a description of the path of the LRN, making it possible to accurately target the LRN to diagnose and alleviate lateral knee pain.